FibroScan-aspartate aminotransferase (FAST) score for monitoring histological improvement in non-alcoholic steatohepatitis activity during semaglutide treatment: post-hoc analysis of a randomised, double-blind, placebo-controlled, phase 2b trialResearch in context - Vincent Wai-Sun Wong; Quentin M. Anstee; Louise M. Nitze; Anja Geerts; Jacob George; Victor Nolasco; Mette S. Kjær; Steen Ladelund; Philip N. Newsome; Vlad Ratziu (EClinicalMedicine, 2023)
Summary: Background: Currently, assessment of candidate pharmacotherapies in patients with non-alcoholic steatohepatitis (NASH) involves invasive liver biopsy. Non-invasive scores, such as the FibroScan-aspartate aminotransferase (FAST) score, are used to identify candidates for therapy, but their ability to assess disease progression or treatment effect is unknown. We aimed to assess the association between FAST score and histological endpoints. Methods: We conducted a post-hoc analysis using data from a prior randomised, double-blind, placebo-controlled, phase 2b trial at 143 sites across 16 countries. Patients (aged 18–75 years) with biopsy-confirmed NASH, fibrosis stage 1–3, and a Non-alcoholic fatty liver disease Activity Score (NAS) ≥4 were enrolled between January 2017 and September 2018, and randomly assigned to receive once-daily subcutaneous semaglutide 0.1, 0.2, or 0.4 mg or placebo for 72 weeks. A subgroup analysis of patients with FAST score and histological data in the pooled semaglutide treatment and placebo arms at baseline and week 72 was performed. The original trial is registered at ClinicalTrials.gov, NCT02970942. Findings: A total of 122 patients were included in this post-hoc analysis (93 received semaglutide and 29 received placebo). FAST score reduction was associated with achieving the primary endpoint of NASH resolution without worsening of fibrosis in the pooled semaglutide group (area under the receiver operating curve 0.69; 95% confidence interval [CI] 0.58, 0.81). Mean FAST score reduction from baseline to week 72 was greatest in patients who met the primary endpoint vs those who did not in both the semaglutide (−0.40 [95% CI –0.84, 0.04] vs −0.22 [95% CI –0.74, 0.30] points; p = 0.002) and placebo groups (−0.25 [95% CI –0.72, 0.23] vs 0.00 [95% CI –0.50, 0.50] points; p = 0.047). Similarly, mean reductions in FAST score at week 72 were greater in those with NAS improvement vs those without in the semaglutide and placebo groups (≥1 point, −0.36 [95% CI –0.82, 0.11] vs −0.08 [95% CI –0.53, 0.38] points [p < 0.001] and −0.25 [95% CI –0.64, 0.14] vs −0.06 [95% CI –0.40, 0.53] points [p = 0.001]; ≥2 points, −0.40 [95% CI –0.86, 0.06] vs −0.14 [95% CI –0.56, 0.28] points [p < 0.001] and −0.29 [95% CI –0.67, 0.09] vs −0.05 [95% CI –0.40, 0.50] points; [p < 0.001]). A FAST score reduction of more than 0.22 points after semaglutide treatment was associated with meeting the primary endpoint (sensitivity 78%; specificity 60%; positive likelihood ratio 1.26; negative likelihood ratio 0.25; odds ratio 4.93). Interpretation: The potential of the FAST score as a non-invasive monitoring tool to identify histological changes following treatment requires further evaluation and validation. Funding: Novo Nordisk A/S.